Improving drip irrigation uniformity by boosting the hydraulic performance of drip lateral pressure regulators - Wang, Xiaoran; Zhang, Chen; Li, Guangyong (International Journal of Agricultural and Biological Engineering, 2024)
Compared with the use of expensive pressure-compensating drip tapes, installing pressure regulators (PRs) at the inlet of cost-effective non-pressure-compensating drip tapes is obviously a more economical technology to achieve precision agriculture. However, most drip lateral PRs may not meet the requirements of the design and use of complex drip irrigation systems (hilly or large-scale systems), and there is seldom research on their application in drip irrigation systems, both restricting the promotion of this precision agriculture technology. In this paper, two types of PRs (A- and B-type) for complex drip irrigation systems are proposed, and compared with two conventional PRs (C- and D-type) under 9 different pressure and flow conditions of the drip irrigation system. The main advantage of A- and B-type PRs over conventional PRs is that their outlet pressures are scarcely affected by inlet pressure and flow. Therefore, A- and B-type PRs not only cope with large submain pressure differences, but also guarantee irrigation uniformity CU up to 90% in drip irrigation systems with different drip-tape lengths (flow range: 350-1400 L/h), while CU can be lower than 80% under the same conditions without PRs or using conventional PRs. When designing drip irrigation systems, the use of A- and B-type PRs can allocate greater pressure deviation to the laterals (hv) to increase the lateral laying length, thus further reducing pipeline network investment. Under the requirements of maximum pressure deviation hv≤40% and submain pressure deviation hv≤20%, the results of hv with A-, B-, C-, and D-type PRs were 30%-35%, 30%-37%, 33%-35%, and 21%-27%, respectively. This research provides a device and method that can improve the irrigation uniformity of drip irrigation systems across a wider application range. Based on this research, users can reasonably select the PRs according to different design standards, significantly enhancing the irrigation uniformity of the system in a cost-effective manner. Key words: microirrigation, pressure regulator, engineering application, irrigation uniformity, drip tape DOI: 10.25165/j.ijabe.20241706.8277 Citation: Wang X R, Zhang C, Li G Y. Improving drip irrigation uniformity by boosting the hydraulic performance of driplateral pressure regulators. Int J Agric & Biol Eng, 2024; 17(6): 185–192.